Neurological disorder in two moose calves ( Alces alces L.) naturally infected with Elaphostrongylus alces - Steen, Margareta; Roepstorff, Lars (Rangifer, 1990)
Two months old moose calves exhibiting neurological signs were videotaped, killed and necropsied. The parasite Elaphostrongylus alces (Steen et al 1989) was found epidurally along the meninges of the spinal cord, and in the muscle faciae of the thoracic and lumbar regions. Progressive inflammatory processes were present in the epineurium, perineurium and endoneurium. Accumulations of inflammatory cells, eosinophils, lymfocytes and macrophages, were found around eggs and larvae and frequently, around regional blood wessels. The neurological disturbances in the moose calves were pronounced, with locomotive abnormalities and ataxia. They showed weakness in the hindquarters, with uncoordinated and swaying movements of the hind legs. In addition, one of the calves was lame on the left forelimb. The muscles of the leg were visibly atrophic. The lesions produced by E. alces at the lumbar nerve roots and in the cauda equina are suggested to be the cause of the clinical signs observed.